AI in Law: How Artificial Intelligence Is Transforming the Legal Profession in Indonesia - Masithoh, Mutia Qori Dewi; Hakim, Hary Abdul; Praja, Chrisna Bagus Edhita; Iswanto, Bambang Tjatur (JUSTITIA JURNAL HUKUM, 2023)
The profess on the development of Artificial Intelligence (AI) has widely transformed a new era in the digital technology, social economic, human need and professional behavior. Eventually, artificial intelligence automates even more aspects of legal profession. Furthermore, AI allows the legal profession to automate lower-level tasks, freeing time to focus on complex analysis and client interaction. The research aims to know the literacy of legal professional on the use of AI. The methods used in this study are normative-empirical legal research. Furthermore, research uses primary data which obtained from questionary survey, secondary data i.e., law, books, journals and other related legal sources for research. Meanwhile, the research will analyze through descriptive qualitatively. The research shows that the literacy level of law enforcers in the use of AI is in the medium category. Data shows that 75% of legal professional shows their positive respond about the implementation of AI in their profession. While other shows, 8% of high percentage and 17% of low percentage.